Interaction of human serum albumin with short polyelectrolytes: a study by calorimetry and computer simulations1. Issue 23 (21st June 2015) - Yu, Shun; Xu, Xiao; Yigit, Cemil; van der Giet, Markus; Zidek, Walter; Jankowski, Joachim; Dzubiella, Joachim; Ballauff, Matthias
<x xml:space="preserve">Abstract</x> Protein–polyelectrolyte complex formation was studied by combining experimental with simulation results. By varying salt concentration and temperature, our study reveals the importance of electrostatics and the release of counterions.